(untitled) (Faridpur Medical College Journal, 2011)
Pyrexia with hepatosplenomegaly is a common problem in medical practice globally, specially in tropical countries. In Bangladesh several tropical diseases as well as hematological malignancies are responsible for such clinical syndrome. Again different tropical diseases vary in endemicity in different regions in Bangladesh. In Present study 50 hospitalized cases of pyrexia with hepatosplenomegaly of 15-50 years of age are included from 01.01.2002 to 30.06.2002 in MMCH to find out their aetiologies. Fever with only hepatomegaly, or with only splenomegaly or hepatosplenomegaly without fever was not included in this study. Duration of fever was two weeks to three months. 35(70%) cases were male and 15(30%) were female. 27(54%) cases were visceral leishmaniasis (kala-azar), 8 (16%) malaria, 6 (12%) Acute leukemia (ALL, AML), 3 (6%) Lymphoma, 3(6%) Enteric fever, 2(4%) CML, 1(2%) Disseminated TB. Although kala-azar and malaria are tow common causes of fever with hepatosplenomegaly, haematological malignancies and tuberculosis should be in mind DOI: 10.3329/fmcj.v5i1.6805 Faridpur Med. Coll. J. 2010;5(1):7-10